2020
DOI: 10.1096/fasebj.2020.34.s1.09583
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Aortic Remodeling with Low Doses of Neprilysin/Angiotensin II Receptor Blockers Sacubitril/Valsartan in a Fibrillin‐1‐Deficient Model of Marfan Syndrome

Abstract: Introduction Sacubitril is a neprilysin inhibitor indicated for heart failure patients with reduced ejection fraction (HFReF), which causes protective natriuretic peptide accumulation. To maximize efficacy and minimize side effects, sacubitril is administered in combination with valsartan, a blood pressure‐lowering angiotensin II receptor blocker (ARB). We and others have shown that ARBs are capable of blood pressure lowering‐independent effects on vascular and lung remodeling, but whether the sacubitril/ARB c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Preliminary data suggest that a low dose of the angiotensin receptor neprilysin inhibitor (ARNI) sacubitril/valsartan can inhibit ascending aorta dilation in the Fbn1 C1039G/+ mouse model to a greater extent than the ARB valsartan alone. 166 Since the doses of both the ARNI and the ARB were titrated to a level not affecting blood pressure, additional neprilysin inhibition is likely to afford additional protection due to its anti-remodeling effects. A first case report of the use of sacubitril/valsartan in an MFS patient showed that this treatment can improve MFS-related cardiomyopathy.…”
Section: Current Medical Managementmentioning
confidence: 99%
“…Preliminary data suggest that a low dose of the angiotensin receptor neprilysin inhibitor (ARNI) sacubitril/valsartan can inhibit ascending aorta dilation in the Fbn1 C1039G/+ mouse model to a greater extent than the ARB valsartan alone. 166 Since the doses of both the ARNI and the ARB were titrated to a level not affecting blood pressure, additional neprilysin inhibition is likely to afford additional protection due to its anti-remodeling effects. A first case report of the use of sacubitril/valsartan in an MFS patient showed that this treatment can improve MFS-related cardiomyopathy.…”
Section: Current Medical Managementmentioning
confidence: 99%